2022
DOI: 10.1111/bph.15812
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and cellular antiarrhythmic and cardiac electrophysiological effects of desethylamiodarone in dog cardiac preparations

Abstract: The data that support the findings of this study are available from the corresponding author upon reasonable request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In both the  and  models, we found that most of the currents were only slightly impacted by the addition of the SK current, with the exception of the rapidly activating delayed rectifier K + current (𝐼 Kr ), which showed a reduction in peak value of 15% and 10% in the  and  models, respectively, and of 𝐼 Ks , which showed a peak reduction of 35% and 31% in the  and  models, respectively. Nonetheless, the values of these two currents in the original and modified models were relatively especially compared to the wide range of physiological variability reported in experiments, up 13% for Kr and 27% 𝐼 [42] (Fig. 18S in the Material).…”
Section: Discussionmentioning
confidence: 73%
“…In both the  and  models, we found that most of the currents were only slightly impacted by the addition of the SK current, with the exception of the rapidly activating delayed rectifier K + current (𝐼 Kr ), which showed a reduction in peak value of 15% and 10% in the  and  models, respectively, and of 𝐼 Ks , which showed a peak reduction of 35% and 31% in the  and  models, respectively. Nonetheless, the values of these two currents in the original and modified models were relatively especially compared to the wide range of physiological variability reported in experiments, up 13% for Kr and 27% 𝐼 [42] (Fig. 18S in the Material).…”
Section: Discussionmentioning
confidence: 73%